Studi Penertiban Tanah Telantar di Indonesia: Analisa Kebijakan Akselerasi dan Administratif terhadap Relevansi Revisi PP 48/2025 - Novandriatur Rizqi; Kurnia Nurindah Sari; Odi Boy Pramana Hutajulu; Shinta Pangesti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Government Regulation Number 48 of 2025 on the Control of Abandoned Land and Areas replaces Government Regulation Number 20 of 2021 and accelerates the process of designating abandoned land from approximately 555 days to around 90 days. This study is entitled to analyze the conformity of such acceleration about the principles of legal certainty and legal protection for landowners, as well as to examine its implications for land rights that are threatened with extinguishment by the state. The research will use basis of the normative juridical method with statute approach and conceptual approaches by examining the Basic Agrarian Law, Government Regulations 20/2021 and 48/2025, as well as relevant agrarian law doctrines and previous studies. The findings indicate that Government Regulation 48/2025 strengthens governmental authority by transferring the power of inventory to the Minister and significantly shortening the stages of evaluation, warning, and designation. However, this acceleration potentially reduces the factual opportunity for right holders, particularly large-scale holders of Right of Cultivation, to demonstrate reutilization of land and regularize permits, thereby creating a risk of imbalance between effective state control and fair legal protection for landowners. Therefore, more detailed implementing regulations on evidentiary procedures and objection mechanisms are required so that the accelerated designation of abandoned land remains consistent with the principles of legal certainty and protection of land rights.